(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Based on the collective realisation that destinations and organisations are becoming increasingly vulnerable to external crises which can negatively impact on the tourism sectors of economies, this article evaluated the strategies that stakeholders utilised towards effective preparedness for external crisis related incidents. The study employed a qualitative case study approach, using interviews and available documents in exploring the crisis preparedness strategies employed by stakeholders in the city of Jos, Plateau State, Nigeria towards addressing the impact of external crisis incidents and threats on their destinations’ tourism industry and subsectors. The study’s field research was based on semi structured interview sessions, covering core questions and probes on the stakeholders’ preparedness for external crises that can affect their tourism sectors, and if there are factors that can affect their efforts towards preparedness for identified crises. The results from the interviews and discussion of findings based on emergent themes from the studies identified a range of recommendations for the study’s destination stakeholders, who were mostly found to be deficient in appropriate crisis preparedness measures, owing to in adequate resources from government, and in some instances, lack of efficient crisis preparedness plan. Of these recommendations, one of the key suggestions was for stakeholders of the city of Jos, Nigeria and similar destination(s) and organisations to adopt or develop a formal crisis preparedness plan, and complete risk assessment on their destination, and other places that could be vulnerable to external crises, for effective crisis preparedness.